Preventive Legal Protection of Trademarks in Indonesia Based on Law Number 20 Of 2016 Concerning Marks and Geographical Indications - Wijanarko, Dwi Seno; Slamet Pribadi (Dinasti Research, 2022)
The legal system of intellectual property rights in Indonesia requires the registration of marks regulated in Article 1 paragraph 5 of the Trademark Law, namely, the right to a mark is an exclusive right granted by the state to registered trademark owners for a certain period of time by using the mark themselves or giving permission for others to use it. The emphasis in the article is that the right to a mark is created due to registration and not because of the first use, as stipulated in Law Number 20 of 2016 concerning Marks and Geographical Indications. Intellectual Property Rights have provided legal protection for individuals who have made discoveries or inventions, putting these individuals in the position of holders of Intellectual Property Rights and granting them exclusive rights to reproduce, manufacture, sell, and distribute his inventions. Apart from giving exclusive rights to inventors, intellectual property rights also provide protection for brand holders, which are usually used to describe reputation (quality), indicating differences between one company and another regarding the existence and goods it produces.